Eksistensi Hukum Adat Minangkabau Dalam Menyelesaikan Tindak Pidana Penculikan Gadis Di Talu Pasaman Barat - Wulanda Septrila Metri; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Indonesia is a country that is based on law. In social life, in addition to the existence of national law, there is also customary law in the midst of the community that was born from the habits and behaviors that have been developed, which are called adat law. This custom or habit will later become a provision called adat law. Whereas customary law and customary law are still used by certain local communities, especially in the Talu Pasaman Barat region where the community still uses customary criminal law to resolve customary criminal acts, specifically the crime of kidnapping girls.The author uses sociological research methods, or often called non-doctrinal theories that try to examine the effectiveness of the application of law in society. This research is descriptive. This research was conducted in Talu, Talamau District, West Pasaman Regency, West Sumatra Province. While the population and sample are all parties related to the problems examined in this study, the source of the data used are primary data, secondary data, and tertiary data, data collection techniques in this study with interviews and document studies.The conclusion that can be drawn from this research is that the existence of customary criminal sanctions such as discarded and fined is still very strong and is still applied in Talu Pasaman Barat, including in resolving cases of abduction of girls resolved through customary law not through positive Indonesian law, so there must be cooperation between the police and traditional stakeholders to make it more efficient.Keywords: Criminal act - kidnapping – Law Adat